Decomposição in situ de macrófitas aquáticas: influência das características de diferentes ecossistemas, atividade celulolítica e interação de macroinvertebrados - Schiavone, Daniele Cristina (2019)
Macrophytes are plants that actively participate in the biogeochemical cycles of aquatic ecosystems. They are important in dynamics and cycling, especially in the carbon cycle. The determination of the decomposition kinetics is a result of the environmental factors in association to the intrinsic characteristics of each species. The present study described the in situ decomposition kinetics of Salvinia auriculata and Urochloa arrecta macrophytes, isolated and mixed, in two types of systems, lentic and lotic, with two types of water, oligotrophic, at Fazzari in São Carlos (SP), and humic water, at Parque das Dunas, in Salvador (BA), with litterbags of thick mesh, in order to allow the interaction of macroinvertebrates, and with fine mesh, without the presence of these organisms. On sample days 1, 5, 15, 30, 60 and 90 (n = 216), the plant samples were placed in the systems in triplicates with the combinations. The limnological variables were analyzed to verify their influence in the decomposition process, as well as measured the organic matter, the total fibers and the enzymatic activity of the detritus cellulase. The decomposition decay parameters were obtained by means of mathematical modeling. Statistics were applied to verify the differences between limnological variables, kinetic and mass loss, aquatic organisms abundances, fiber content in detritus and enzymatic decomposition activities. Environmental factors such as dissolved oxygen, nitrogen, conductivity and carbon had influences in some treatments, regardless of the type of system. Salvinia auriculata presented a slower decomposition with respect to Urochloa arrecta isolated, so that the mixture of species was maintained with intermediate values in the majority of treatments of the Fazzari system. As for the study done at Parque das Dunas, there were no significant differences in the loss of mass and in the time of decomposition of the different treatments. It also did not present significant alteration related to the macrophyte type. Therefore, humic water was the most relevant factor in this environment. The presence of macroinvertebrates did not affect the decomposition kinetics. Urochloa arrecta presented lower fiber contents compared to Salvinia auriculata, the difference was mainly in relation to the lignin content. The enzymatic kinetics were mainly affected by the type of macrophytes, being the largest accumulation obtained with Urochloa arrecta. The lentic and lotic systems did not present differences even in relation to the type of mesh used. In short, the decomposition process was influenced by both intrinsic and extrinsic factors, depending on the experimental conditions tested.